Autobiografia Niny Berberowej Podkreślenia moje — historia i struktura formalna dzieła - Banasiuk, Elżbieta (Przegląd Rusycystyczny, 2009)
AUTOBIOGRAPHY THE ITALICS ARE MINE BY NINA BERBEROVA — THE HISTORY AND STRUCTURE OF THE WORK Summary This article presents the history and structure of a famous and contradictory work — Nina Berberova’s autobiography, written in 1960–1966. In spite of the long time passed, no com-plete and competent analysis of the work has been made, due to its complexity. АВТОБИОГРАФИЯ НИНЫ БЕРБЕРОВОЙ КУРСИВ МОЙ— ИСТОРИЯ И СТРУКТУРА ПРОИЗВЕДЕНИЯ Резюме В настоящей статье представлены история и структура известной автобиографии Нины Берберовой, написанной в 1960–1966 гг. Несмотря на уходящее время и полемику вокруг книги, до сих пор не проводился полный, всесторонний анализ произведения отсутствует.